2004
DOI: 10.1001/archinte.164.18.1978
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Diagnostic Accuracy of Natriuretic Peptides for Heart Failure

Abstract: Background:The diagnosis of heart failure is difficult, with both overdiagnosis and underdiagnosis occurring commonly in practice. Natriuretic peptides have been proposed as a possible test for assisting diagnosis. We assessed the diagnostic accuracy of brain natriuretic peptide (BNP), including a comparison with atrial natriuretic peptide (ANP).Methods: Electronic searches were conducted of MEDLINE and EMBASE from January 1994 to December 2002 and handsearches of reference lists of included studies. We includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
183
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(201 citation statements)
references
References 46 publications
(44 reference statements)
10
183
1
7
Order By: Relevance
“…31,32 Because these analyses require a single measure of accuracy for each study and many reported multiple APRI thresholds, we calculated the average DOR among all thresholds per study. 33 The disadvantage of the DOR as an outcome parameter is that summary estimates of sensitivity and specificity are not directly available. It is, however, possible to obtain an estimate of sensitivity by specifying a value of specificity, or vice versa.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Because these analyses require a single measure of accuracy for each study and many reported multiple APRI thresholds, we calculated the average DOR among all thresholds per study. 33 The disadvantage of the DOR as an outcome parameter is that summary estimates of sensitivity and specificity are not directly available. It is, however, possible to obtain an estimate of sensitivity by specifying a value of specificity, or vice versa.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Regarding histopathological classification systems, 11 studies used Ishak, 4 used METAVIR, 4 used Scheuer, and 3 used Batts and Ludwig. Nineteen studies included HCVmonoinfected patients (n ϭ 3,822), 17,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and 4 included HIV/HCV-co-infected patients (n ϭ 444). [48][49][50][51] Biopsy quality was considered acceptable in only 4 of the 22 studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Natriuretic peptides are released from the heart in response to myocardial tension and increased intravascular volume and provide accurate tests for the diagnosis of heart failure compared with echocardiography [1]. B-type natriuretic peptide (BNP) and the N-terminal proBNP fragment (NTproBNP) are both powerful predictors of outcome in patients with heart failure at all stages of disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…Echocardiography has been used to determine cardiac function before treatment with NPLD [29,40]. BNP as marker for cardiac dysfunction could be used for therapeutic monitoring [41][42][43]. However, BNP levels can currently not be used instead of echocardiography and the predictive value of BNP elevations remains uncertain [44,45].…”
Section: Discussionmentioning
confidence: 99%